Tapping Brazil's labour potential: Trends and insights - Dean Spinanger (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
Examining labour market developments in Brazil, the fastest growing economy in Latin America over the twenty years through 1985, means dealing with the impact and interactions of policies in a multifacetted country the size of a continent, harboring very large differences in population densities and income levels. However, as the title of the paper already implies, no attempt is made to do justice to all the manifold issues engendered within such a complex economy . The paper is thus limited to focussing on macroeconomic and sectoral labour market developments - be they on the demand or supply side of labour/human capital - and in this context on the impact of policies within the formal sector. The basic thrust of the evidence presented thereby is aimed at determining to what extent labour market policies in Brazil (especially as they impacted on the manufacturing industry) allowed labour to be efficiently employed.
Keywords: 330